Pregnancy During the Global COVID-19 Pandemic: Canadian Experiences of Care - Rudrum, Sarah (Frontiers in Sociology, 2021)
Drawing on journal entries written by a cohort of pregnant Canadians, this article explores how responses to the COVID-19 pandemic shaped access to and experiences of maternity care. Variance in practices among jurisdictions and among provider groups meant that participants had diverse experiences. Nevertheless, I identify clear shared concerns, including fear over giving birth with no familial support, the need for better communications, and challenges entailed when needing to switch providers or travel for care during a state of emergency. Despite a universal health care system, there are gaps and inequities in access to appropriate maternity care in Canada; the pandemic exposed existing access challenges.